Phase II National Study: Job Satisfaction and Workplace Environment Among Community Pharmacists in Lebanon: Pre and Post Economic Crisis - Salaheddin, Amira Talaat (2024)
Background: Pharmacists play a crucial role in healthcare systems worldwide. High levels of pharmacist job satisfaction are critical for the delivery of quality, patient-centered care. In Lebanon, pharmacists face unique challenges stemming from an ongoing economic crisis, the COVID-19 pandemic, and a shifting healthcare landscape. Aims: This study aims to assess the job satisfaction of Lebanese pharmacists during the ongoing economic and healthcare challenges. Specifically, it seeks to evaluate the impact of Lebanon’s economic collapse, medication shortages, and the COVID-19 pandemic on pharmacists’ working conditions, autonomy, and overall job satisfaction. The study also aims to compare the results to those obtained in Phase I (2016). Methods: This is a phase II national study where a stratified random sample of pharmacists from all governorates of Lebanon was obtained from a complete list of Lebanese pharmacists. The survey was administered via a link sent to pharmacists through SMS and WhatsApp, with follow-up calls to encourage participation. The questionnaire utilized in phase I (2016) was updated to include questions on the impact of the economic crisis and COVID-19 on Lebanese pharmacists’ job satisfaction. Results: Notable differences between Phase I and Phase II emerged regarding overall job satisfaction. Average weekly working hours decreased from 59.2 hours in Phase 1 to 49.8 hours in Phase II. Regarding autonomy, more pharmacists in Phase 2 (85.8%) agreed they had opportunities to utilize their skills and knowledge. Drug shortages had a significant impact on pharmacy operations, with 72.6% of pharmacists in Phase II reporting business disruptions due to shortages. Pharmacists also reported an increase in the frequency of prescription interventions, particularly related to dosage errors and drug-drug interactions, with intervention rates rising from 23.7% in 2016 to 51.1% in 2024. Conclusion: This study provides valuable insights into the perspectives of Lebanese community pharmacists, focusing on key aspects such as job satisfaction, autonomy, and the challenges faced during the COVID-19 pandemic and the ongoing economic crisis. While certain aspects of pharmacists' experiences have evolved by 2024, financial dissatisfaction and overall job dissatisfaction persist, emphasizing the need for greater support and resources to address job-related stress and enhance the prescription system, thereby reducing the frequency of interventions.